2008
DOI: 10.1017/s0022112007009184
|View full text |Cite
|
Sign up to set email alerts
|

The collective dynamics of self-propelled particles

Abstract: We have proposed a method for the dynamic simulation of a collection of self-propelled particles in a viscous Newtonian fluid. We restrict attention to particles whose size and velocity are small enough that the fluid motion is in the creeping flow regime. We have proposed a simple model for a self-propelled particle, and extended the Stokesian Dynamics method to conduct dynamic simulations of a collection of such particles. In our description, each particle is treated as a sphere with an orientation vector p,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 44 publications
4
50
0
1
Order By: Relevance
“…These tendencies were in satisfactory qualitative agreement with previous experimental observations. In the model of Mehandia & Nott (2008), however, coherent structures similar to former experimental observations were not mentioned. The difference may have come from the near-field hydrodynamics between interacting particles.…”
Section: Coherent Structures In a Bacterial Suspensionmentioning
confidence: 63%
“…These tendencies were in satisfactory qualitative agreement with previous experimental observations. In the model of Mehandia & Nott (2008), however, coherent structures similar to former experimental observations were not mentioned. The difference may have come from the near-field hydrodynamics between interacting particles.…”
Section: Coherent Structures In a Bacterial Suspensionmentioning
confidence: 63%
“…2 confirm the core assumption of local alignment in self-propelled particle models (8)(9)(10)(11)(12)(13) and demonstrate that short-range correlations extending to the third nearest neighbor are sufficient to produce collective motion. The spatial correlations observed in our system originate from hydrodynamic (25)(26)(27)(28)(29) and excluded-volume (29-31) interactions between bacteria, and from physical intertwining of flagella of neighboring bacteria (20,(32)(33)(34). It has been shown that both excluded-volume (35) and hydrodynamic (28) interactions can lead to local orientational order.…”
Section: G-imentioning
confidence: 85%
“…The spatial correlations observed in our system originate from hydrodynamic (25)(26)(27)(28)(29) and excluded-volume (29-31) interactions between bacteria, and from physical intertwining of flagella of neighboring bacteria (20,(32)(33)(34). It has been shown that both excluded-volume (35) and hydrodynamic (28) interactions can lead to local orientational order. Physical intertwining of flagella has been directly demonstrated with fluorescent imaging (33,34), but the interaction due to intertwining has not been quantified in experiments.…”
Section: G-imentioning
confidence: 85%
“…2D simulations showed that long-range hydrodynamic interactions result in strong reorientation rates Ω i HI that are sufficient to entirely suppress motility-induced phase separation of squirmers [346]. Simpler non-squirming swimmers simulated with the lattice Boltzmann method in 2D [348,349] and with Stokesian dynamics in a monolayer in 3D [350] showed some clustering. We performed three-dimensional MPCD simulations of squirmers and strongly confined them between two parallel plates, such that they could only move in a monolayer (quasi-2D geometry) [161].…”
Section: Microswimmers With Hydrodynamic Interactionsmentioning
confidence: 98%